In vitro and in vivo assessment of skim milk with and without egg yolk on canine spermatozoa incubated at 4ºC - Díaz, J. D. (2013)
The aims of this study were to assess and compare the effect of skim milk with (MEY) and without (SMI) egg yolk on canine spermatozoa incubated at 4ºC in vitro and to evaluate the efficacy of MEY in vivo. Also, the effect of semen cooled storage before freezing was also evaluated in vitro. The ejaculates of 10 dogs were collected, pooled, centrifuged, and divided into 4 aliquots and diluted in one of the following 4 diluents: Prostatic fluid (PRO), commercial diluent (COM), SMI, or MEY. Extended samples were stored at 4°C and evaluated daily for 6 days. Percentage of total (P < 0.01) and progressive (P < 0.01) motility, intact acrosomes (P < 0.05), and positive endosmosis (P < 0.01) decreased over time in the diluents, with COM and PRO having as the best and the worst performances, respectively. Furthermore, MEY motility differed from PRO (P < 0.01) and SMI (P < 0.01) but not COM. Acrosome integrity was higher in MEY when compared to SMI (P < 0.05). Sixteen pairs of dogs were randomly assigned to either fresh undiluted semen (n = 8) or to 24-h cooled MEY diluted semen (n = 8). Seven (87.5%; P > 0.1) bitches from each group became pregnant and whelped normally. MEY extended semen samples were cooled for 2, 24, or 48 h at 4°C, and a second dilution was performed prior to freezing and thawing. Post-thaw total and forward sperm motility decreased with increasing cooled storage (P < 0.05), although no significant differences in total or forward motility, normal acrosomes, positive endosmosis, live spermatozoa, or positive endosmosis were found between 2 and 24 h storage. These in vitro and in vivo results show that MEY can be considered a simple, inexpensive, and efficient diluent for canine semen chilling. Furthermore, MEY could be successfully frozen after 1 day of cooled storage.